2012
DOI: 10.1089/jmf.2011.1968
|View full text |Cite
|
Sign up to set email alerts
|

Fraction of Macroporous Resin from Smilax china L. Inhibits Testosterone Propionate–Induced Prostatic Hyperplasia in Castrated Rats

Abstract: The present study was conducted to evaluate the effect of a fraction of macroporous resin (FMR), a bioactive component of Smilax china L., on benign prostatic hyperplasia (BPH) in castrated rats induced by testosterone propionate. Rats were randomly divided into five groups: the negative control group (sham-operated), the model group, two FMR-treated groups (at doses of 300 mg/kg and 600 mg/kg of body weight), and the positive control group (treated with finasteride at the dose of 3 mg/kg). Drugs were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous studies indicated that testosterone level was not shown to have similar patterns with DHT level. 33,34 Testosterone plays an important role in the development of the male reproductive system. Testosterone level was measured to observe the changes in serum and prostate tissue after TP injection.…”
mentioning
confidence: 99%
“…Previous studies indicated that testosterone level was not shown to have similar patterns with DHT level. 33,34 Testosterone plays an important role in the development of the male reproductive system. Testosterone level was measured to observe the changes in serum and prostate tissue after TP injection.…”
mentioning
confidence: 99%
“…Men with severely enlarged prostate suffer from obstructive and irritative symptoms including nocturia, irreversible bladder failure, and greater risk of acute urinary retention, which affect the quality of life [ 3 , 4 ]. Although the pathogenesis of BPH has not been fully elucidated, aetiology is explained in ways of ageing, hormonal alterations, growth factors, and inflammatory cell infiltration [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, effect of various herbal medicines on BPH and its associated complications has been reported in various studies (9-11). …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of herbal medicines and natural products is increasing because of fewer side effects ( 7 , 8 ). On the other hand, effect of various herbal medicines on BPH and its associated complications has been reported in various studies ( 9 - 11 ).…”
Section: Introductionmentioning
confidence: 99%